IMPLEMENTASI PENDIDIKAN TERPADU DAN PROGRAM TEPAT GUNA DALAM UPAYA PEMBERDAYAAN MASYARAKAT - Helmi, Helmi; Sya, Mega Febriani (Universitas Djuanda, 2018)
The social dedication is one of the Teacher Training Facultys Program. The students face the real social situation and transform their class kowledge to solve the real social program. The real Social Working was held in Sukakarya Village tha a part of Bogor Regency, West Java. Those programs had been done for forty days by twenty students. Previous study had detected the unqualified PAUD teachers, there was no social committe concerning the children and teenagers development. Many of the social members were not aware of the important of health and good education. The economic problem was also a big deal to solve. The program had been progressed based on those problem appeared in Sukakarya village. Some programs that had been done are the accompanied of PAUD school administration, the renovation of PAUD class, the seminar to improve PAUD teachers capability, Quranic Study included Al Quran room for kids and teenagers, the increasing of the known of the letter of the alphabet, the healthy training program, the development of the creative economic program, the smart corner in order to facilitate the children for literature and finally, this program ended after the celebration of Independence Day.